Exponentially Fitted Trapezoidal Scheme for a Stochastic Oscillator (Journal of Computational Mathematics, 2021)
This paper applies exponentially fitted trapezoidal scheme to a stochastic oscillator. The scheme is convergent with mean-square order 1 and symplectic. Its numerical solution oscillates and the second moment increases linearly with time. The numerical example verifies the analysis of the scheme.
Keywords: Exponentially fitted trapezoidal scheme; Symplectic; mean-square order; Second moment.